2010
DOI: 10.1590/s0100-69912010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da profilaxia do tromboembolismo venoso em hospital de grande porte

Abstract: The results show alarming levels of thromboprophylaxis inadequacy, inacceptable in these times of well-established published guidelines. Therefore, a continuing education program should be implanted for all the assistance team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
(20 reference statements)
1
4
0
7
Order By: Relevance
“…It was found that there was no difference between rates of thromboprophylaxis noncompliance in clinical and surgical patients, as was also observed by Fuzinatto et al 17 and Carneiro et al 20 Underutilization of chemoprophylaxis was the most common reason for noncompliance among both clinical and surgical patients. This has also been observed by other authors, 10,17,20,21 who documented underutilization among patients at high risk of development of VTE and its complications, reporting evidence of noncompliance between what is recommended by thromboprophylaxis protocols and what actually takes place in hospitals.…”
Section: Discussionsupporting
confidence: 68%
“…It was found that there was no difference between rates of thromboprophylaxis noncompliance in clinical and surgical patients, as was also observed by Fuzinatto et al 17 and Carneiro et al 20 Underutilization of chemoprophylaxis was the most common reason for noncompliance among both clinical and surgical patients. This has also been observed by other authors, 10,17,20,21 who documented underutilization among patients at high risk of development of VTE and its complications, reporting evidence of noncompliance between what is recommended by thromboprophylaxis protocols and what actually takes place in hospitals.…”
Section: Discussionsupporting
confidence: 68%
“…Vale ressaltar, a baixa taxa de insucesso, somente 2.5%, num grupo de 79 pacientes que foram submetidos apenas à profilaxia mecânica para TVP 15 . Outros estudos servem para nos guiar quantificando a realização da profilaxia realizada de forma correta, apontando ou identificando números de condutas inadequadas 16 . É exposto que a profilaxia através da cinesioterapia para membros inferiores, compressão e contração intermitente de tríceps sural para ativar esta bomba muscular, que ao ser ativada ou comprimida promove uma diminuição da estase venosa auxiliando também no aumento do retorno venoso 10 .…”
Section: Discussionunclassified
“…16 , 17 A multicenter study carried out in other organizations of the State of São Paulo found a frequency of 38.92% of thromboprophylaxis for patients admitted to clinical and surgical wards. Carneiro et al 5 demonstrated that 86% of the surgical patient in an ICU received any type of prophylaxis for VTE. Only one study, performed in 2.000, evaluated patients submitted to THA in Brazil, demonstrating that 80% of patients were submitted to some type of drug prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…( 16 , 17 ) Estudo multicêntrico conduzido em outros centros do Estado de São Paulo encontrou frequência de 38,92% de tromboprofilaxia para pacientes internados em alas clínicas e cirúrgicas. Carneiro et al ( 5 ) demonstraram que 86% dos pacientes cirúrgicos internados em uma unidade de terapia intensiva receberam algum tipo de profilaxia para TEV Somente um estudo, realizado em 2,000, avaliou pacientes submetidos à ATQ no Brasil, demonstrando que 80% dos pacientes foram submetidos a algum tipo de profilaxia medicamentosa. ( 19 )…”
Section: Discussionunclassified